2018
DOI: 10.1007/s10877-018-0132-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting delayed cerebral ischemia after subarachnoid hemorrhage using physiological time series data

Abstract: To develop and validate a prediction model for delayed cerebral ischemia (DCI) after subarachnoid hemorrhage (SAH) using a temporal unsupervised feature engineering approach, demonstrating improved precision over standard features. 488 consecutive SAH admissions from 2006 to 2014 to a tertiary care hospital were included. Models were trained on 80%, while 20% were set aside for validation testing. Baseline information and standard grading scales were evaluated: age, sex, Hunt Hess grade, modified Fisher Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Meiring et al [ 7 ] showed that common physiological parameters such as HR and MAP and treatment given can predict mortality on the ICU on subsequent days. Other applications are prediction of delayed cerebral ischaemia after subarachnoid haemorrhage [ 9 ], prediction of favourable neurological outcome among children on the ICU with critical illness [ 8 ] or prediction of impending sepsis in neonates [ 28 ]. Although it also has been attempted to use physiological parameters to predict outcome 6 to 12 months after TBI, data used are solely measured before admission or incorporate the whole ICU admission period, hampering (early) clinical assistance [ 4 , 5 , 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meiring et al [ 7 ] showed that common physiological parameters such as HR and MAP and treatment given can predict mortality on the ICU on subsequent days. Other applications are prediction of delayed cerebral ischaemia after subarachnoid haemorrhage [ 9 ], prediction of favourable neurological outcome among children on the ICU with critical illness [ 8 ] or prediction of impending sepsis in neonates [ 28 ]. Although it also has been attempted to use physiological parameters to predict outcome 6 to 12 months after TBI, data used are solely measured before admission or incorporate the whole ICU admission period, hampering (early) clinical assistance [ 4 , 5 , 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, confounding factors, consequences of the initial trauma (like brain swelling, metabolic crises and inflammation) and the individual response to therapy during ICU admission are not included. Because full supportive care for a certain amount of time from initial presentation is recommended to maximize the potential for recovery from primary and secondary damage [ 6 ], extending prognostic models with early physiological monitoring data might improve the outcome prediction accuracy as has been shown in studies on the ICU for pathologies other than TBI [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…predicting outcomes of ruptured aneurysms [33]; predicting ischemia after aneurysmal subarachnoid hemorrhage [34];…”
Section: Application Of Artificial Intelligence In Vascular Neurosurgmentioning
confidence: 99%
“…There is thus a need for better prediction models. In the article published by Park and colleagues in the February 2019 issue [20], the authors set out to develop and validate a new prediction model, using a temporal unsupervised feature engineering approach. For model development, they used data collected retrospectively from 488 patients admitted to their unit/hospital with a SAH.…”
Section: Predicting Delayed Cerebral Ischemia After Subarachnoid Hemomentioning
confidence: 99%